Analisis Kestabilan Lereng Highwall Berdasarkan Tingkat Kejenuhan Dengan Metode Probabilitas Pada Tambang Batubara PT. X Kalimantan Timur - Yudho Dwi Galih Cahyono (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2022)
The existence of water on the slope will cause serious technical problems, especially in the stability of mine slope. Because of this reason, it is necessary to analyze the stability of slope in order to keep the slope in stable condition. The slope is analyzed under unsaturated and saturated conditions by calculating the value of safety factor and the probability of sliding. Rock samples were tested for physical and mechanical characteristic as input data for slope analysis on slide 6.0 program. The results of the analysis show that the FK value of unsaturated slope with a height of 120 meters and an angle of 30 degrees is 1.7. While the saturated slope with the same geometry has FK value of 0.961. Then the geometry of saturated slope is changed to 120 meters with an angle of 25 degrees and it’s got FK value of 1.6. While the probability of landslides for unsaturated slope is 2.3% and saturated slope is 3.0%. There is a significant difference related to the effect of water on the barrels, namely the difference in FK value of 0.846 and PK value of 9.2%. This difference occurs because the existence of water has increased the density of rock and decreased the value of cohesion so that the value of the driving force on the slope becomes larger and causes a high potential for landslides.